Deconstructing soil detachment: integrated assessment of soil properties, root characteristics, and hydraulics under diverse land uses on the Chinese loess plateau - JianFang Wang; JiaMing Li; GuoBin Liu; WeiWei Ma; Bing Wang (CATENA, 2026)

Investigations on ballistic behaviour of additive manufactured 316L stainless steel corrugated sandwich panels filled with ultra-high performance geopolymer concrete - Jian Liu; Cunyi Li; Guobin Li; Sihao Lin; Ming-Xiang Xiong; Jianguang Fang (Engineering Structures, 2026)

NAT10-mediated ac4C acetylation of PKM2 promotes papillary thyroid carcinoma through regulating glycolysis - Guobin Qiu; Yinghuan Cen; Yuan Li; Jiaan Ye; Sufen Li; Xin Li (Journal of Molecular Histology, 2026)

Nyström least-squares collocation for regional geoid modeling with a large dataset - Xun Zhang; Guobin Chang; Hefang Bian; Xiannan Han; Houpu Li (Earth Science Informatics, 2026)

A circular agriculture model based on vegetable tailing fermentation broth: a case study of cabbage production - Junjie Cui; Rongrong Zhang; Mingle Yang; Tingting Mu; Shilei Luo; Long Li; Guobin Zhang (Bioresource Technology Reports, 2026)

Ferritin-mediated copper delivery induces dual cell death across diverse leukemia types - Huaiji Wang; Wenjing Wang; Wenqiang Sun; Feifan Liu; Caopei Zheng; Xiaoyun Lin; Yuhua Li; Weier Bao; Xiaoming Hu; Guobin Qi; Feng Li; Guanghui Ma; et al. (Science Bulletin, 2026)

Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

A century-scale dynamic modeling of demolition waste metabolism and associated global warming impact in China’s urban residential sector - Wenbo Zhao; Jian Li Hao; Guobin Gong; Zhiqin Ni; Thomas B. Fischer; Vivian W.Y. Tam; Yunfei Xia (Waste Management, 2026)

Deep visual multi-omics reveals intra-tumor heterogeneity of gene expression and immunophenotype in colorectal cancer - Shijun Lei; Wanshan Ning; Hongyan Zhang; Qun Chen; Luming Xu; Shaobo Tian; Xiaoqiong Li; Wenyu Liu; Mengxi Xiang; Feng Liu; Guobin Wang; Lin Wang; et al. (Science Bulletin, 2026)

Age-dependent MADS-box factors recruit PtTFL2 to orchestrate dormancy depth in Pinus tabuliformis - Kai Qu; Guobin Liu; Qijing Xia; Ting Liao; Liqin Guo; Yanan Zhang; Yousry A. El-Kassaby; Wei Li (Plant Science, 2026)

Territorial space security evaluation and zonal governance based on security pattern theory: A case study of China’s land border areas - Guobin Ma; Rucheng Lu; Guanhai Gu; Pengcheng Wang; Yiyun Li; Liguo Zhang (Advances in Space Research, 2026)

Sediment-mediated coupling of hyporheic exchange and land use drives macroinvertebrate community structure - Mengdan Guan; Wei Hong; Nan Li; Jinxi Song; Guobin Fu; Shilei Yang; Haoying Zhang; Mengyang Yang; Haozheng Sun (Journal of Cleaner Production, 2026)

The role of particle shape irregularity in the constitutive behavior of aeolian dune sand: Insights from DEM simulations - Minyi Zhu; Shiva Prashanth Kumar Kodicherla; Guobin Gong; Kai Li; Naveen Revanna; Hu Zheng (Bulletin of Engineering Geology and the Environment, 2026)

Iris time-frequency map visual feature-based cluster matching: A universal domain adaptation method for propulsion shafting fault diagnosis - Congyue Li; Guobin Li; Pengfei Xing; Dexin Cui; Yijin Sui; Hongpeng Zhang (Ocean Engineering, 2026)

Effects of polystyrene nanoplastics on tomato plant growth, fruit yield and quality - Mingyuan You; Ting Zhou; Jiahui Yan; Jingyue Ma; Tingting Kong; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Food Chemistry, 2026)

SlNAC63-SlbHLH71 module enhances tomato saline-alkali tolerance via regulating JA biosynthesis and ROS scavenging - Xiangguang Meng; Zhen Kang; Xiaoyan Liu; Qingpeng Li; Zhenglun Li; Zihan Chu; Songshen Hu; Zhi Zhang; Guobin Li; Tianlai Li; Xiaohui Hu (Theoretical and Applied Genetics, 2026)

A lightweight toolkit of synthetic promoters and regulatory sRNAs for gene expression regulation in industrial Streptococcus - Tianai Kong; Yanan Sun; Guobin Yin; Guosen Cheng; Jianghua Li; Guocheng Du; Jian Chen; Yang Wang (Systems Microbiology and Biomanufacturing, 2026)

eAodeMar: a lightweight and real-time occluded marine vessel detection network for embedded marine platforms - Yuanyuan Wang; Mingyu Wang; Jianqiang Shi; Zuo Ni; Guobin Li (Frontiers in Marine Science, 2026)
Introduction The detection of occluded marine vessels is critical for the safe navigation and operation of unmanned surface vehicles (USVs). While image-based detection methods have achieved substantial accuracy, their high computational and memory requirements prohibit deployment on resource-constrained embedded platforms. To address this, we propose eAodeMar (efficient AodeMar), a lightweight version built upon our prior AodeMar model, specifically designed for efficient occluded marine vessel detection. Methods The efficiency of eAodeMar is achieved by integrating Ghost convolution modules into both the backbone and the feature fusion network, significantly reducing model parameters and computational load while maintaining accuracy. To ensure practical applicability, the optimized model is deployed on an embedded GPU platform (Jetson Xavier NX), incorporating dedicated structural refinement and inference acceleration techniques. Results Extensive experiments on the public MVDD13 dataset demonstrate that eAode- Mar reduces parameter count and computational load by 7.00% and 0.89%, respectively, with only a marginal accuracy drop of 0.42%, while achieving a remarkable 42.12% improvement in inference speed. When deployed on the Jetson Xavier NX device, it attains a real-time detection rate of 28.57 FPS on the SMD video stream. Discussion These comprehensive results validate that eAodeMar effectively balances high precision with high efficiency in occlusion-prone maritime environments. The model demonstrates strong potential for real-world ocean engineering applications, offering a practical solution for real-time detection on embedded systems.

A scene-adapted lightweight YOLO-LD model for dead fish detection in recirculating aquaculture systems - Weihong Wei; Maochun Wei; Hongcheng Li; Guobin Hong (Aquaculture International, 2026)

A progressive domain separation network incorporating iris time-frequency maps for open-set diagnosis of ship propulsion shafting - Congyue Li; Guobin Li; Pengfei Xing; Dexin Cui; Yijin Sui; Hongpeng Zhang (Ocean Engineering, 2026)

High-resolution chronostratigraphic framework and spatiotemporal evolution of Carboniferous-Permian source rocks in the Junggar Basin and its periphery - Zhangshuai Hou; Xiangdong Wang; Dongming Zhi; Yong Tang; Qiong Wu; Hua Zhang; Jian Cao; Dongsheng Xiao; Guobin Fu; Menglin Zheng; Xuefeng Qi; Yaofeng Cai; et al. (Science China Earth Sciences, 2026)

Plant–soil feedback alters plant–soil–microbial nutrient status and elemental-limitation status during secondary succession - Yong Cao; Zemin Ai; Xinghua Li; Mengjia Hou; Yuyan Yao; Yi Deng; Huan Liu; Jiaoyang Zhang; Guobin Liu; Sha Xue (Soil Ecology Letters, 2025)

An innovative theoretical model for optimizing ball diameter in tumbling mills - Yunxiao Li; Qingfei Xiao; Yanxiong Fu; Saizhen Jin; Guobin Wang; Mengtao Wang; Boyuan Sun; Houyuan Tian; Xiaobo Liu; Jiahao Tian (Minerals Engineering, 2025)

Effects of mixed plantations with N-fixing species on microbial-driven soil multifunctionality are climate-dependent: Evidence from the Loess Plateau of China - Lu Zhang; Wancai Wang; Lei Deng; Ting Li; Lirong Liao; Shilong Lei; Guobin Liu; Chao Zhang (Forest Ecology and Management, 2025)

Stable and efficient n-type perylene diimides radical as cathode interlayer with wide thickness tolerance for organic solar cells - Lin Hu; Senmei Lan; Guobin Shen; Fang Wang; Yingzhi Jin; Zhen Su; Jia Yao; Mengzhen Du; Zheng Yan; Wei Li; Dan Zhou; Erjun Zhou; et al. (Chemical Engineering Journal, 2025)

Color matters: Investigating stress recovery in VR-simulated interior environments using fNIRS and anxiety measures - Dehan JIA; Wenan LI; Xingkai WANG; Yuyang JIANG; Guobin XIA; Luwen YU (Building and Environment, 2025)

Synergistic Enhancement of Plant Drought Tolerance by PYL and ABA—A Review - Rongrong Zhang; Shilei Luo; Long Li; Tingting Mu; Peng Wang; Guobin Zhang (Journal of Plant Growth Regulation, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Synthesis of novel phthalide bearing thiazole, 1,3,4-oxadiazole, and oxime ether groups as potential antifungal agents - Yong Li; Taotao Wu; Guobin Chen; Jian He; Yong Zhang; Qin Zhang; Pengfei Zhou; Wenzhang Chen; Lingling Fan (Molecular Diversity, 2025)

Floatable Janus nanofiber membrane driven by photothermal bubbles: A novel platform for efficient photocatalytic water purification - Kelin Wang; Guobin Li; Xiaolong Bie; Jiaqi Yu; Xing Guo; Hanxue Jia; Pengxin Liu; Weimin Kang; Zhenbang Han; Yong Liu (Journal of Cleaner Production, 2025)

Distribution and control of the pest darkling beetles (Coleoptera, Tenebrionidae) at the world heritage site Mogao Grottoes - Feiqing Zhu; Fasi Wu; Yuxin Chen; Jie Li; Guobin Zhang; Long Li; Zhang Chen (International Biodeterioration & Biodegradation, 2025)

Shifts in Genome Size and Energy Utilization Strategies Sustain Microbial Functions Along an Aridity Gradient - Xiaojun Wang; Wancai Wang; Lei Deng; Ting Li; Shilong Lei; Lu Zhang; Lirong Liao; Zilin Song; Guobin Liu; Chao Zhang (Global Change Biology, 2025)
Microbes acquire energy to sustain their survival and function through the decomposition of organic carbon (C) or by oxidizing atmospheric trace gases (e.g., H 2 , CO, CH 4 ). However, how these two microbial energy‐acquisition strategies change along environmental gradients and the underlying mechanisms are unclear. This study investigated the energy strategies and genomic traits of soil microbiomes along a natural aridity gradient, ranging from semi‐humid forests to arid deserts. By analyzing 374 metagenome‐assembled genomes from 13 microbial phyla, we found that the most prevalent microbes are metabolically versatile aerobes that use atmospheric trace gases to support aerobic respiration, C fixation, and N, P, and S cycling. Soil microbes adapt genomic traits associated with reduced energy expenditure in more arid soils, including smaller genome sizes, lower GC content, and fewer 16S rRNA gene copies. Microbial communities in diverse arid habitats are capable of utilizing organic compounds and the oxidation of trace gases (e.g., H 2 , CO, CH 4 , and H 2 S) as energy sources. However, the utilization of organic energy decreased while reliance on trace gas oxidation increased with increasing aridity. Higher consumption rates of H 2 , CO, and CH 4 in desert soils from ex situ culture experiments confirmed that increased aridity stimulates microbial oxidation of atmospheric trace gases. This shift in energy utilization was strongly correlated with declining soil organic C levels. As organic C decreased along the aridity gradient, the abundance of trace gas oxidizers (both specialized and multi‐gas oxidizers) increased significantly, while that of non‐oxidizers declined. Trace gas oxidizers exhibited smaller genomes, lower 16S rRNA operon copy numbers, and slower predicted growth rates, indicative of oligotrophic lifestyles. In contrast, copiotrophic non‐oxidizers had larger genomes and faster growth rates. These findings reveal that microbial communities adapt their genomic traits and energy‐acquisition strategies to sustain functionality across aridity gradients, enhancing our understanding of soil microbiome responses to climate change.

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

MoTe2 quantum dot-mediated nano-heterojunction and lattice strain regulation for high-performance CsPbI2Br perovskite solar cells - Yue Yuan; Guobin Li; Fei Zhao; Jiabao Li; Ziting Qi; Jiangtao Guo; Peizhi Yang (Chemical Engineering Journal, 2025)

Plant and microbial β diversities are better predictors of ecosystem functioning than their α diversities, but aridity weakens these associations - Lu Zhang; Shilong Lei; Rong Qian; Raúl Ochoa-Hueso; Xiangtao Wang; Jie Wang; Lirong Liao; Guobin Liu; Qiang Li; Chao Zhang (Plant and Soil, 2025)

Tomato DC1 domain protein SlCHP16 interacts with the 14–3-3 protein TFT12 to regulate flower development - Guobin Li; Jiafa Wang; Licheng Xiao; Chunli Zhang; Dedi Zhang; Guo Ai; Minghua Yao; Changxing Li; Zonglie Hong; Zhibiao Ye; Junhong Zhang (Plant Science, 2025)

Halophyte inspired solar-driven salt extractor for saline soil remediating - Zixuan Liu; Junhui Li; Yongxu Liu; Qi Sun; Dengchao Liang; Xuan Yang; Wenwen Zhao; Yafang Zhang; Hong Liu; Jiebing Tang; Weijia Zhou; Guobin Xue (Chemical Engineering Journal, 2025)

Improving intestinal barrier function and intestinal microbiome of weaned piglets fed a low-protein diet through tryptophan and N-Acetylglutamic acid supplementation - Shichao Liu; Zhiyuan Tai; Muzhi Li; Rui Zhang; Guobin Shao; Jiatai Guo; Weixing Lu (Tropical Animal Health and Production, 2025)

Synthesis and antifungal activities of small molecule arylthiazolamine derivatives - Xu Zhong; Jian He; Taigui Ma; Guobin Chen; Yong Zhang; Min Zhang; Lei Tang; Yong Li; Lingling Fan (Molecular Diversity, 2025)

Silicon Promotes Na+ Compartmentalization and Mineral Uptake in Zucchini Seedlings to Maintain Physiological Homeostasis and Alleviate Salt Stress - Rongrong Zhang; Guoshuai Wang; Shilei Luo; Long Li; Tingting Mu; Peng Wang; Guobin Zhang (Journal of Plant Growth Regulation, 2025)

Unlocking the power of manganese-doped MoS2 hollow nanotubes: A game-changing Fenton co-catalyst for ciprofloxacin degradation - Jingyu Liu; Yongyou Hu; Xian Li; Yuming Liu; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Chemical Engineering Journal, 2025)

Claudin-11 plays a pivotal role in the clathrin-mediated endocytosis of influenza A virus - Xiaofei Yu; Zixin Ni; Yifan Wang; Jingfei Wang; Guohua Deng; Jianzhong Shi; Huihui Kong; Yongping Jiang; Guobin Tian; Chengjun Li; Yoshihiro Kawaoka; Hualan Chen; et al. (Science China Life Sciences, 2025)

The light-responsive transcription factor SlBBX20 improves low-temperature resistance of Solanum lycopersicum by affecting photosynthetic capacity, antioxidant capacity, and osmotic adjustment - Yongbo Ma; Manling Chen; Yingjin Xing; Zhenglun Li; Ting Zhou; Haijing Yan; Jiahui Yan; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Plant Cell Reports, 2025)

A review of the interaction mechanisms between jasmonic acid (JA) and various plant hormones, as well as the core regulatory role of MYC2 - Tingting Mu; Shilei Luo; Long Li; Rongrong Zhang; Peng Wang; Guobin Zhang (Plant Science, 2025)

Investigation on alignment state evolution of ship propulsion shafting based on chaotic characteristics of vibration signals - Lixun Lu; Guobin Li; Pengfei Xing; Wenzhi He; Zhaoyang Feng; Hongpeng Zhang (Ocean Engineering, 2025)

Achieving ultra-low latent heat of water evaporation in capillary water by regulating hydrophilic groups and pore structure of cellulose/chitosan gel - Dengchao Liang; Jiebin Tang; Qi Sun; Wenwen Zhao; Junhui Li; Yongxu Liu; Zixuan Liu; Xuan Yang; Hong Liu; Guobin Xue (Carbohydrate Polymers, 2025)

Regulation mechanisms of tea residue-based carbon dots in water-induced full-color emission and applications of visual ratio water sensors in organic solvents and WLEDs - Chao Yong; Ying Lei; Jian Du; Yinghui Liu; Yu Li; Fan Ye; Lin Xu; Guobin Ni; Shaowu Zhang (Analytica Chimica Acta, 2025)

SAG mill ball diameter semi-theory based on pebble fracture strength and DEM validation - Yunxiao Li; Qingfei Xiao; Guobin Wang; Boyuan Sun; Chao Zheng; Saizhen Jin; Qingkai Wang (Minerals Engineering, 2025)

Deep soil carbon pool responses to climate change in the Chinese Loess Plateau - Guangyao Gao; Binbin Li; Karl J. Niklas; Yuanyuan Huang; Mingxiang Xu; Guobin Liu; Bojie Fu (Science Bulletin, 2025)

Spectral fingerprints of DOM-tungsten interactions: Linking molecular binding to conformational changes - Weijun Li; Guobin Liu; Ming Lei; Yaoyu Zhou; Haojie Cui; Huihui Du (Journal of Hazardous Materials, 2025)

The effect of particle elongations on incremental behavior of granular materials using discrete element method - Minyi Zhu; Guobin Gong; Shiva Prashanth Kumar Kodicherla; Kai Li; Yu Huang; Hu Zheng (Computers and Geotechnics, 2025)

Carboxyl-functionalized montmorillonite composite hydrogel containing alginate as a highly efficient adsorbent for simultaneous removal of cationic dyes and heavy metal ions - Yang He; Dong Lin; Guobin Jiang; Li Jiang; Jingwen Xiao; Huanghao Li; Lihua Zhou; Shaohua Gou (Journal of Water Process Engineering, 2025)

Applying digital technologies in construction waste management for facilitating sustainability - Wenbo Zhao; Jian Li Hao; Guobin Gong; Thomas Fischer; Yong Liu (Journal of Environmental Management, 2025)

Ratiometric fluorescent paper chip for monitoring the freshness of high protein foods - Guobin Mao; Yuan Zeng; Chunmin Qiu; Guangmiao Ding; Leyao Li; Lixin Ma; Junbiao Dai; Wen Yin; Yingxin Ma (Analytica Chimica Acta, 2025)

Metagenomics reveals the characteristics and potential spread of microbiomes and virulence factor genes in the dairy cattle production system - Yimin Zhuang; Shuai Liu; Jianxin Xiao; Tianyu Chen; Duo Gao; Yiming Xu; Wen Jiang; Jingjun Wang; Guobin Hou; Sumin Li; Xinjie Zhao; Yanting Huang; et al. (Journal of Hazardous Materials, 2024)

Correction: Roles of estrogen receptors during sexual reversal in pelodiscus sinensis - Guobin Chen; Tong Zhou; Jizeng Cao; Xiang Li; Chengjun Zhu; Long Wang; Guiwei Zou; Hongwei Liang (Molecular Biology Reports, 2024)

Roles of estrogen receptors during sexual reversal in Pelodiscus sinensis - Guobin Chen; Tong Zhou; Jizeng Cao; Xiang Li; Chengjun Zhu; Long Wang; Guiwei Zou; Hongwei Liang (Molecular Biology Reports, 2024)

The Response of Grassland Production to N and P Fertilizer Management Mediated soil Nematode Community in Qinghai-Tibet Plateau of China - YuanZe Li; HuaKun Zhou; QiFan Zhao; WenJing Chen; HongFei Liu; Bing Yang; Yang Wu; GuoBin Liu; Sha Xue (Journal of Soil Science and Plant Nutrition, 2024)

Analyte-induced hindrance in the RCA-assisted CRISPR/Cas12a system for homogeneous protein assays - Guobin Mao; Qiaoyu Li; Ziying Zhang; Wei Huang; Qian Luo; Junbiao Dai; Weiren Huang; Yingxin Ma (Analytica Chimica Acta, 2024)

Investigation on Dynamic Behaviors of Ship Propulsion Shafting with Misalignment Based on Stochastic Uncertainty Models - Pengfei Xing; Feng Zhao; Xiaoliang He; Guobin Li (Journal of Marine Science and Engineering, 2024)
To investigate the effect of stochastic uncertainty on the dynamic behaviors of ship propulsion shafting with misalignment, a stochastic uncertainty model of ship shafting is established based on nonparametric theory and stochastic excitation. Numerical simulation and experimental verification of the dynamic behaviors are carried out using a ship shafting test bench. The results indicate that stochastic uncertainty has a significant effect on the dynamic behaviors of shafting with misalignment. With an increase in stochastic uncertainty, the fractional frequency appears in the spectrum, and the axis trajectory becomes more complex and gradually deviates from the center orbit. Therefore, to ensure the safe navigation of ships, it is necessary to consider the stochastic uncertainty in dynamic research on the misalignment of shafting.

A Hybrid Approach Based on the SR-HWPT-PDF for Identifying Early Fault Signals in Rolling Bearings - Zhaoyang Feng; Pengfei Xing; Guobin Li; Lu Zhang; Lixun Lu; Xiaoliang He; Hongpeng Zhang (Journal of Marine Science and Engineering, 2024)
An approach combining the stochastic resonance, the harmonic wavelet packet transforms and the probability density function was proposed to obtain the early fault signal of a rolling bearing. Firstly, an adaptive variable-scale stochastic resonance was employed to detect the frequency range of the rolling bearing’s fault signal based on the improved signal-to-noise ratio, and then the harmonic wavelet packet transforms and the probability density function were utilized to extract and identify the fault signal of the rolling bearings from the detected signals. The case studies show that the proposed method can effectively obtain the early fault signals of the outer race, inner race and rolling element in the rolling bearings despite not knowing the frequency band distribution, and that the early fault diagnosis of the rolling bearings can be achieved.

Sensitive and rapid identification of pathogens by droplet digital PCR in a cohort of septic patients: a prospective diagnostic study - Zhenping Wu; Yake Yao; Xi Li; Hongliu Cai; Guobin Wang; Wenqiao Yu; Hui Lou; Qi Chen; Zhu Zeng; Hao Yu; Jiang Xia; Yunsong Yu; et al. (Infectious Diseases, 2024)

Catalyzing sustainability through prefabrication: Integrating BIM-LCA for assessing embodied carbon in timber formwork waste - Jian Li Hao; Wenbo Zhao; Guobin Gong; Wenting Ma; Lihong Li; Yuzhuo Zhang (Sustainable Chemistry and Pharmacy, 2024)

Fault diagnosis method of marine centrifugal fan based on adversarial network learning - Congyue Li; Guobin Li; Dexin Cui; Yihuai Hu (Ocean Engineering, 2024)

Numerical and experimental investigation on the whirling vibration characteristic of ship propulsion shafting under multi-source uncertainty - Lixun Lu; Guobin Li; Pengfei Xing; Honglin Gao; Yuchao Song; Hongpeng Zhang (Ocean Engineering, 2024)

Thermal distillation of hypersaline waters toward zero liquid discharge via spontaneously siphon-channeling crystallized salt - Yafang Zhang; Liping Yang; Junhui Li; Wenwen Zhao; Yongxu Liu; Meng Ding; Guobin Xue (Chemical Engineering Journal, 2024)

Hexafluoropropylene oxide trimer acid (HFPO-TA) disrupts sex differentiation of zebrafish (Danio rerio) via an epigenetic mechanism of DNA methylation - Dan Yang; Fanghua Li; Xiaohui Zhao; Shasha Dong; Guobin Song; Haonan Wang; Xiaoying Li; Guanghui Ding (Aquatic Toxicology, 2024)

A longitudinal multimodal MRI study of the visual network in postoperative delirium - Guobin Zhang; Beier Qi; Haoyi Li; Xiaokang Zhang; Jian Chen; Haiyun Li; Bin Jing; Huawei Huang (Brain Imaging and Behavior, 2024)

Unraveling deformation mechanism of the Fukang fold-and-thrust belt: Insight into intracontinental orogenesis of the Bogda Mountain, NW China - Yu Zhen; Dengfa He; Xuan Chen; Di Li; Guobin Fu; Wenjian Guo (Marine and Petroleum Geology, 2024)

Unveiling the Pharmacological Role of Human Deubiquitinating Enzymes in Temozolomide Response of Glioblastoma Cells - Chunguang Yang; Yifei Li; Qifan Wu; Jiayi Tang; Min Chen; Baoyu Zhang; Bowen Li; Yunfei Qin; Guobin Huang; Yize Zhang; Feng Zhi; Kunpeng Liu (Cell Biochemistry and Biophysics, 2024)

Nine-year fertilization promoted C sink and mediated microbial nutrient utilization in alpine meadow soil aggregates - Leilei Qiao; Huakun Zhou; Zhanhui Wang; Wenjing Chen; Yuanze Li; Yang Wu; Guobin Liu; Sha Xue (Applied Soil Ecology, 2024)

Enabling long cycle aluminum-sulfur batteries via structurally stable Co, N-doped graphene-CNTs covalently bonded hybrid - Jinsheng Lv; Guobin Lai; Tian Yang; Xiaotong Sun; Feng Liu; Wenpeng Wu; Mengfan Shi; Guantong Wang; Kun Gao; Xiangyang Li; Nan Chen (Chemical Engineering Journal, 2024)

Biomass carbon stock and allocation of planted and natural forests in the Loess Plateau of China - Binbin Li; Guangyao Gao; Karl J. Niklas; Yiqi Luo; Mingxiang Xu; Guobin Liu; Bojie Fu (Agricultural and Forest Meteorology, 2024)

A Method for Multi-AUV Cooperative Area Search in Unknown Environment Based on Reinforcement Learning - Yueming Li; Mingquan Ma; Jian Cao; Guobin Luo; Depeng Wang; Weiqiang Chen (Journal of Marine Science and Engineering, 2024)
As an emerging direction of multi-agent collaborative control technology, multiple autonomous underwater vehicle (multi-AUV) cooperative area search technology has played an important role in civilian fields such as marine resource exploration and development, marine rescue, and marine scientific expeditions, as well as in military fields such as mine countermeasures and military underwater reconnaissance. At present, as we continue to explore the ocean, the environment in which AUVs perform search tasks is mostly unknown, with many uncertainties such as obstacles, which places high demands on the autonomous decision-making capabilities of AUVs. Moreover, considering the limited detection capability of a single AUV in underwater environments, while the area searched by the AUV is constantly expanding, a single AUV cannot obtain global state information in real time and can only make behavioral decisions based on local observation information, which adversely affects the coordination between AUVs and the search efficiency of multi-AUV systems. Therefore, in order to face increasingly challenging search tasks, we adopt multi-agent reinforcement learning (MARL) to study the problem of multi-AUV cooperative area search from the perspective of improving autonomous decision-making capabilities and collaboration between AUVs. First, we modeled the search task as a decentralized partial observation Markov decision process (Dec-POMDP) and established a search information map. Each AUV updates the information map based on sonar detection information and information fusion between AUVs, and makes real-time decisions based on this to better address the problem of insufficient observation information caused by the weak perception ability of AUVs in underwater environments. Secondly, we established a multi-AUV cooperative area search system (MACASS), which employs a search strategy based on multi-agent reinforcement learning. The system combines various AUVs into a unified entity using a distributed control approach. During the execution of search tasks, each AUV can make action decisions based on sonar detection information and information exchange among AUVs in the system, utilizing the MARL-based search strategy. As a result, AUVs possess enhanced autonomy in decision-making, enabling them to better handle challenges such as limited detection capabilities and insufficient observational information.

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Multi-fault diagnosis of district heating system based on PCA_BP neural network - Shoujun Zhou; Xiangrui Liu; Yongsheng Tian; Chi Zhang; Fachang Li; Guobin Jiang (Process Safety and Environmental Protection, 2024)

Decarbonizing prefabricated building waste: Scenario simulation of policies in China - Wenbo Zhao; Jian Li Hao; Guobin Gong; Wenting Ma; Jian Zuo; Luigi Di Sarno (Journal of Cleaner Production, 2024)

Promoted adsorption-photocatalysis synergistic removal of contaminants via surface regulation by a tree-like nanofiber membrane substrate - Minghui Zhang; Zhenbang Han; Guobin Li; Xiaolong Bie; Xingyang Gao; Jin Zhao; Xiaoming Zhao (Journal of Environmental Chemical Engineering, 2024)

Fuzzy Logic-Based Decision-Making Method for Ultra-Large Ship Berthing Using Pilotage Data - Yibo Li; Guobin Song; Tsz-Leung Yip; Gi-Tae Yeo (Journal of Marine Science and Engineering, 2024)
As seafarers are involved in Maritime Autonomous Surface Ships (MASS), except for those in the fourth level of autonomy, the decision making of autonomous berthing should be carried out and be understood by human beings. This paper proposes a fuzzy logic-based human-like decision-making method for ultra-large ship berthing, which considers locations, ship particulars and the natural environment, and these factors are treated as the input variables. The IF–THEN rules are then established after the fuzzification of the input variables and are used for fuzzy inference to derive the decision of ship handling. It can be implemented in the decision-making system for safe navigation or be included in the process of autonomous berthing. The pilotage data are collected with nautical instruments and a distance measurement system during the berthing process, which are used to validate the proposed model and calculate the speed and turn errors. The overall and individual error of the decision-making model is in a reasonable and small range, which indicates that the model has good accuracy. The results of this research offer theoretical and practical insights into the development of a human-like decision-making method for autonomous navigation in port waters and maritime safety management in the shipping industry. The model can be further applied to develop a more widely applicable decision-making system for autonomous navigation in confined waters.

Research on Abrasive Particle Target Detection and Feature Extraction for Marine Lubricating Oil - Chenzhao Bai; Jiaqi Ding; Hongpeng Zhang; Zhiwei Xu; Hanlin Liu; Wei Li; Guobin Li; Yi Wei; Jizhe Wang (Journal of Marine Science and Engineering, 2024)
The hydraulic oil of marine equipment contains a large number of abrasive contaminants that reflect the operating condition of the equipment. In order to realize the detection of particulate contaminants, this research first proposes a shape-based classification method for oil abrasive particles, designs an oil abrasive particle collection system, and constructs a new dataset. After that, the research introduces deep learning target detection technology in computer vision, and uses GhostNet to lighten the network structure, the CBAM (Convolutional Block Attention Module) attention mechanism to improve the generalization ability of the model, and the ASPP module to enhance the model sensory wildness, respectively. A lightweight target detection model, WDD, is created for the identification of abrasive particles. In this study, the WDD model is tested against other network models, and the mAP value of WDD reaches 91.2%, which is 4.8% higher than that of YOLOv5s; in addition, the detection speed of the WDD model reaches 55 FPS. Finally, this study uses real ship lubricating oils for validation, and the WDD model still maintains a high level of accuracy. Therefore, the WDD model effectively balances the accuracy and detection speed of marine oil abrasive particle detection, which is superior to other oil abrasive particle detection techniques.

Episodic evolution of intracontinental orogenic deformation: Insight from the southern Bogda fold-and-thrust belt of the Tianshan Mountains, NW China - Yu Zhen; Dengfa He; Di Li; Xuan Chen; Guobin Fu (Tectonophysics, 2024)

Numerical calculation and experimental investigation of the dynamic alignment of ship propulsion shafting based on Latin hypercube stochastic finite element - Lixun Lu; Guobin Li; Pengfei Xing; Honglin Gao; Yuchao Song; Hongpeng Zhang (Ocean Engineering, 2024)

Genomics and metabolic characteristics of simultaneous heterotrophic nitrification aerobic denitrification and aerobic phosphorus removal by Acinetobacter indicus CZH-5 - Zuhao Chen; Yongyou Hu; Guanglei Qiu; Donghui Liang; Yiyong Li; Jianhua Cheng; Yuancai Chen; Guobin Wang; Jieyun Xie; Xiaoqiang Zhu (Bioresource Technology, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Presence of a long nuclear-localization signal sequence in homeodomain transcription factor Nkx1.2 - Xinyi Li; Lihui Chen; Xinyuan Wang; Chen Sun; Guangdong Ji; Guobin Hu; Zhenhui Liu (Journal of Oceanology and Limnology, 2024)

Intermediate irrigation with low fertilization promotes soil nutrient cycling and reduces CO2 and CH4 emissions via regulating fungal communities in arid agroecosystems - Wancai Wang; Zhencheng Ye; Jing Li; Guobin Liu; Qixiao Wu; Zhaoyang Wang; Guoqin He; Wende Yan; Chao Zhang (Journal of Environmental Management, 2024)

Exploring Acoustic Wave Propagation and Equivalent Path in Quasi-Porous Medium of Loose Coal Mass - Jun Guo; Changming Chen; Guobin Cai; Hu Wen; Shuai Li (Natural Resources Research, 2024)

Green renovation of existing public buildings in China: A synergy mechanism of state-owned enterprises based on evolutionary game theory - Yulong Li; Zhuang Wang; Wenqing Liang; Fan Yang; Guobin Wu (Journal of Cleaner Production, 2024)

Promoting photo-Fenton reactions by anchoring Fe doped g-C3N4 onto an amidoxime-functionalized fibrous support for organic contaminants removal - Guobin Li; Zhenbang Han; Tao Wang; Minghui Zhang; Qiaoqiao Liu; Tong Zhang; Xiaoming Zhao (Journal of Water Process Engineering, 2023)

An electrochemically transformed multifunctional binder network simultaneously strengthens the interphase stability and mechanical integrity of silicon anodes - Weibo Huang; Yan Wang; Xiang Li; Huaiwei Feng; Linze Lv; Yuchen Li; Guobin Zhu; Honghe Zheng (Chemical Engineering Journal, 2023)

Effects of Long-Term Warming on Microbial Nutrients Limitation of Soil Aggregates on the Qinghai-Tibet Plateau - Wenjing Chen; Huakun Zhou; Leilei Qiao; Yuanze Li; Yang Wu; Jiaying Zhai; Guobin Liu; Sha Xue (Journal of Soil Science and Plant Nutrition, 2023)

Effects of deterministic assembly of communities caused by global warming on coexistence patterns and ecosystem functions - Wenjing Chen; Huakun Zhou; Yang Wu; Jie Wang; Ziwen Zhao; Yuanze Li; Leilei Qiao; Kelu Chen; Guobin Liu; Coen Ritsema; Violette Geissen; Xue Sha (Journal of Environmental Management, 2023)

A review of stochastic finite element and nonparametric modelling for ship propulsion shaft dynamic alignment - Lixun Lu; Guobin Li; Pengfei Xing; Honglin Gao; Yuchao Song (Ocean Engineering, 2023)

High-strength, self-reinforcing and recyclable multifunctional lignin-based polyurethanes based on multi-level dynamic cross-linking - Zhiyi Huang; Huan Wang; Jiahao Du; Xiaochun Liu; Guoyi Pan; Xingshan Yin; Wenjing Lin; Xiaofeng Lin; Yingjuan Sun; Guobin Yi; Li Niu (Chemical Engineering Journal, 2023)

Long-term warming impacts grassland ecosystem function: Role of diversity loss in conditionally rare bacterial taxa - Wenjing Chen; Huakun Zhou; Yang Wu; Jie Wang; Ziwen Zhao; Yuanze Li; Leilei Qiao; Kelu Chen; Guobin Liu; Coen Ritsema; Violette Geissen; Xinrong Guo; et al. (Science of The Total Environment, 2023)

Effect of plant-soil feedback on soil microbial co-occurrence network depends on the stage of secondary succession - Zemin Ai; Yi Deng; Xinghua Li; Jiaoyang Zhang; Hongfei Liu; Hongwei Xu; Guobin Liu; Xue Sha (Rhizosphere, 2023)

High-efficient degradation of chloroquine phosphate by oxygen doping MoS2 co-catalytic Fenton reaction - Jingyu Liu; Yongyou Hu; Xian Li; Chun Xiao; Yueyue Shi; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Hazardous Materials, 2023)

Degradation of sulfamethoxazole by super-hydrophilic MoS2 sponge co-catalytic Fenton: Enhancing Fe2+/Fe3+ cycle and mass transfer - Chun Xiao; Yongyou Hu; Qitian Li; Jingyu Liu; Xian Li; Yueyue Shi; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Hazardous Materials, 2023)

Integrated and effective management of muck waste under the platform governance mode for a circular economy - Weiwei Wu; Youying Yin; Jian Li Hao; Wenting Ma; Guobin Gong; Shiwang Yu (Environmental Science and Pollution Research, 2023)

Dynamic analyses of composite corrugated sandwich plates filled with magnetorheological elastomer resting on elastic foundation - Jing Zhao; Guobin Fan; Jialin Guan; Hui Li; Zhijiang Gao; Hui Ma (Engineering Structures, 2023)

Enhanced grain boundary conductivity of Gd and Sc co-doping BaZrO3 proton conductor for proton ceramic fuel cell - Guobin Qin; Jinxiao Bao; Jianquan Gao; Fei Ruan; Shengli An; Zhenbo Wang; Li Li (Chemical Engineering Journal, 2023)

SlGH3.15, a member of the GH3 gene family, regulates lateral root development and gravitropism response by modulating auxin homeostasis in tomato - Guo Ai; Rong Huang; Dedi Zhang; Miao Li; Guobin Li; Wangfang Li; John K. Ahiakpa; Yikui Wang; Zonglie Hong; Junhong Zhang (Plant Science, 2023)

Carbon stock and sequestration of planted and natural forests along climate gradient in water-limited area: A synthesis in the China's Loess plateau - Binbin Li; Guangyao Gao; Yiqi Luo; Mingxiang Xu; Guobin Liu; Bojie Fu (Agricultural and Forest Meteorology, 2023)

Effect of anthocyanins on mechanical and physicochemical properties of wheat dough - Yueqin Li; Li Xie; Xintong Jiang; Gaoyang Cai; Guobin Zhu; Zhi Zheng; Fengru Liu (Journal of Cereal Science, 2023)

Variations in soil aggregate stability and organic carbon stability of alpine meadow and shrubland under long-term warming - Leilei Qiao; Huakun Zhou; Zhanhui Wang; Yuanze Li; Wenjing Chen; Yang Wu; Guobin Liu; Sha Xue (CATENA, 2023)

Multi-responsive graphene quantum dots hybrid self-healing structural color hydrogel for information encoding and encryption - Jingye Yan; Guoyi Pan; Wenjing Lin; Zilun Tang; Jieheng Zhang; Jiaxin Li; Wenping Li; Xiaofeng Lin; Hongsheng Luo; Guobin Yi (Chemical Engineering Journal, 2023)

Effect of plant–plant interactions and drought stress on the response of soil nutrient contents, enzyme activities and microbial metabolic limitations - Lie Xiao; Xuxu Min; Guobin Liu; Peng Li; Sha Xue (Applied Soil Ecology, 2023)

Soil biochemical index-based assessment of the effect of drought stress on the rhizosphere soil quality in three typical grass species in the Loess Plateau, China - Lie Xiao; Meng Zhao; Guobin Liu; Peng Li; Fangyuan Liu; Sha Xue (Journal of Soils and Sediments, 2022)

Long-term warming does not affect soil ecoenzyme activity and original microbial nutrient limitation on the Qinghai—Tibet Plateau - Yuanze Li; Huakun Zhou; Wenjing Chen; Yang Wu; LeiLei Qiao; ZiRan Yan; GuoBin Liu; Sha Xue (Soil Ecology Letters, 2022)

A Multi-Method Approach to Identify the Natural Frequency of Ship Propulsion Shafting under the Running Condition - Pengfei Xing; Lixun Lu; Guobin Li; Xin Wang; Honglin Gao; Yuchao Song; Hongpeng Zhang (Journal of Marine Science and Engineering, 2022)
In order to identify the natural frequency of ship propulsion shafting under the running condition, a multi-method approach that combines Duffing Oscillator, harmonic wavelet packet transform, and probability density function is proposed. An experimental investigation on the natural frequency of running propulsion shafting is conducted on the ship propulsion shafting test bench, and the natural frequency response of running propulsion shafting under different alignment states is obtained from the measured bearing vibration signal. The results show that the natural frequency of propulsion shafting can be excited under the running condition, but its response is feeble. When the alignment state of the propulsion shafting gradually changes with the elevation of the front stern bearing, the identified natural frequency of the propulsion shafting shows an upward trend. In contrast, its amplitude shows a downward trend. Therefore, the proposed approach can identify the natural frequency of the ship propulsion shafting from the measured bearing vibration signal under the running condition.

Studying bona fide SARS-CoV-2 biology in a BSL-2 biosafety environment using a split-virus-genome system - Yingxin Ma; Guobin Mao; Weishan Yang; Guoqiang Wu; Guoqiang Li; Xiaoying Li; Xin Lin; Junnan Lu; Shijun Zhao; Wei Zhao; Junbiao Dai; Xian-En Zhang (Science China Life Sciences, 2022)

Drought prediction in the Yunnan–Guizhou Plateau of China by coupling the estimation of distribution algorithm and the extreme learning machine - Qiongfang Li; Yao Du; Zhennan Liu; Zhengmo Zhou; Guobin Lu; Qihui Chen (Natural Hazards, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Ecoenzymatic stoichiometry reflects the regulation of microbial carbon and nitrogen limitation on soil nitrogen cycling potential in arid agriculture ecosystems - Zhencheng Ye; Jie Wang; Jing Li; Chao Zhang; Guobin Liu; Qinge Dong (Journal of Soils and Sediments, 2022)

Mdivi-1 Modulates Macrophage/Microglial Polarization in Mice with EAE via the Inhibition of the TLR2/4-GSK3β-NF-κB Inflammatory Signaling Axis - Xiaoqin Liu; Xiaojuan Zhang; Xiaojie Niu; Peijun Zhang; Qing Wang; Xiuhua Xue; Guobin Song; Jiezhong Yu; Guoping Xi; Lijuan Song; Yanhua Li; Cungen Ma (Molecular Neurobiology, 2022)

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Sorptive removal of methylene blue from water by magnetic multi-walled carbon nanotube composites - Guobin Song; Anqi Li; Yawei Shi; Wanran Li; Haonan Wang; Chunchao Wang; Ruijuan Li; Guanghui Ding (Environmental Science and Pollution Research, 2021)

Diversity and co-occurrence network modularization of bacterial communities determine soil fertility and crop yields in arid fertigation agroecosystems - Zhencheng Ye; Jing Li; Jie Wang; Chao Zhang; Guobin Liu; Qin’ge Dong (Biology and Fertility of Soils, 2021)

Long Non-coding RNA GAS5 Worsens Coronary Atherosclerosis Through MicroRNA-194-3p/TXNIP Axis - Yanbing Li; Yu Geng; Boda Zhou; Xuejiao Wu; Ou Zhang; Xiaonan Guan; Yajun Xue; Siyuan Li; Xianjing Zhuang; Jie Zhou; Meng Chang; Guobin Miao; et al. (Molecular Neurobiology, 2021)
It is formerly conducted that long non-coding RNA growth arrest-specific 5 (GAS5) is involved in the process of coronary atherosclerosis (AS). The regulatory effects of GAS5 on the microRNA (miR)-194-3p/thioredoxin-interacting protein (TXNIP) axis in AS have been insufficiently explored yet. Thereafter, this work is started from GAS5/miR-194-3p/TXNIP axis in AS. AS rats were modeled to obtain their coronary vascular tissues and endothelial cells (ECs), in which GAS5, miR-194-3p, and TXNIP expression were tested. ECs were identified by immunohistochemistry. The mechanism among GAS5, miR-194-3p, and TXNIP was determined. ECs were transfected with inhibited GAS5 or overexpressed miR-194-3p to decipher their functions in proliferation and apoptosis of ECs in AS. Raised GAS5 and TXNIP and degraded miR-194-3p expression levels exhibited in AS. GAS5 bound to miR-194-3p while miR-194-3p targeted TXNIP. Depleting GAS5 or restoring miR-194-3p enhanced proliferation and depressed apoptosis of ECs in AS. This work clearly manifests that inhibited GAS5 facilitates the growth of ECs through miR-194-3p-targeted TXNIP in AS, consolidating the basal reference to the curing for AS.

Appropriate Ammonium/Nitrate Mitigates Low Light Stress in Brassica pekinensis by Regulating the Nitrogen Metabolism and Expression Levels of Key Proteins - Linli Hu; Yue Wu; Mohammed Mujitaba Dawuda; Weibiao Liao; Jian Lv; Yutong Li; Jihua Yu; Jianming Xie; Zhi Feng; Guobin Zhang; Alejandro Calderón-Urrea (Journal of Plant Growth Regulation, 2021)

Greenhouse gas emissions from semi-aerobic bioreactor landfills with different vent-pipe diameters - Guobin Jiang; Dan Liu; Weiming Chen; Zhiyong Han; Qibin Li (Environmental Science and Pollution Research, 2021)

Progress and prospects of applied research on physical geography and the living environment in China over the past 70 years (1949–2019) - Fahu Chen; Shaohong Wu; Peng Cui; Yunlong Cai; Yili Zhang; Yunhe Yin; Guobin Liu; Zhu Ouyang; Wei Ma; Linsheng Yang; Duo Wu; Jiaqiang Lei; et al. (Journal of Geographical Sciences, 2021)

A new approach for optimizing air pollutant emissions using Newtonian relaxation and the coupled WRF-CAMx model: a case study in Xuzhou city, China - Yanpeng Li; Zibin Bai; Guobin Wang (Arabian Journal of Geosciences, 2020)

Role of Chromatin Remodeling Genes and TETs in the Development of Human Midbrain Dopaminergic Neurons - Li Xiang; Guobin Huang; Wenjing Shu; Chunli Gong; Nan Cao; Rui Chen; Jixi Li; Hao Lu; Gaofeng Jiang (Stem Cell Reviews and Reports, 2020)

Measured behaviors of an oversized irregular basement excavation and its surrounding responses in thick soft clay - Guobin Liu; Jian Guo; Mingyu Li; Tao Qin; Pei Huang (Arabian Journal of Geosciences, 2020)

Direct and indirect effects of elevated CO2 and nitrogen addition on soil microbial communities in the rhizosphere of Bothriochloa ischaemum - Lie Xiao; Guobin Liu; Peng Li; Sha Xue (Journal of Soils and Sediments, 2019)

Helmert transformation solutions combination and update with new measurements - Shengquan Li; Bing Ji; Guobin Chang; Peng Lin; Shaofeng Bian (Acta Geodaetica et Geophysica, 2019)

Effect of nitrogen addition on the decomposition and release of compounds from fine roots with different diameters: the importance of initial substrate chemistry - Hang Jing; Peng Zhang; Jingjing Li; Xu Yao; Guobin Liu; Guoliang Wang (Plant and Soil, 2019)

Impact of leachate recirculation frequency on the conversion of carbon and nitrogen in a semi-aerobic bioreactor landfill - Ziyin Luo; Weiming Chen; Peng Wen; Guobin Jiang; Qibin Li (Environmental Science and Pollution Research, 2019)

Macrophages but not Astrocytes Harbor HIV DNA in the Brains of HIV-1-Infected Aviremic Individuals on Suppressive Antiretroviral Therapy - Allen Ko; Guobin Kang; Julian B. Hattler; Hadiza I. Galadima; Junfeng Zhang; Qingsheng Li; Woong-Ki Kim (Journal of Neuroimmune Pharmacology, 2019)

Vaccination of poultry successfully eliminated human infection with H7N9 virus in China - Xianying Zeng; Guobin Tian; Jianzhong Shi; Guohua Deng; Chengjun Li; Hualan Chen (Science China Life Sciences, 2018)

Removal of refractory organic pollutants in reverse-osmosis concentrated leachate by Microwave–Fenton process - Aiping Zhang; Zhepei Gu; Weiming Chen; Qibin Li; Guobin Jiang (Environmental Science and Pollution Research, 2018)

Identification of key genes fluctuated induced by avian leukemia virus (ALV-J) infection in chicken cells - Guohong Chen; Zhiteng Li; Shuai Su; Guobin Chang; Lingling Qiu; Pengfei Zhu; Yang Zhang; Qi Xu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Soil resistance to concentrated flow and sediment yields following cropland abandonment on the Loess Plateau, China - Zheng Zhang; Qiang Li; Guobin Liu; Dengfeng Tuo (Journal of Soils and Sediments, 2017)

First report of the melon stem rot disease in protected cultivation caused by Pseudomonas fluorescens - Chenghua Zhang; Tao Lin; Jufen Li; Guobin Ma; Yiwen Wang; Pinkuan Zhu; Ling Xu (Journal of Plant Diseases and Protection, 2016)

VRC01 antibody protects against vaginal and rectal transmission of human immunodeficiency virus 1 in hu-BLT mice - Ming Sun; Yue Li; Zhe Yuan; Wuxun Lu; Guobin Kang; Wenjin Fan; Qingsheng Li (Archives of Virology, 2016)

Effect of root architecture on structural stability and erodibility of topsoils during concentrated flow in hilly Loess Plateau - Qiang Li; Guobin Liu; Zheng Zhang; Dengfeng Tuo; Mingxiang Xu (Chinese Geographical Science, 2015)

Effects of progressive drought stress on the physiology, antioxidative enzymes and secondary metabolites of Radix Astragali - Xin Jia; Chuangshu Sun; Guangyue Li; Guobin Li; Guilin Chen (Acta Physiologiae Plantarum, 2015)

Recent changes in precipitation extremes in the Heihe River basin, Northwest China - Aifang Cheng; Qi Feng; Guobin Fu; Jiankai Zhang; Zongxing Li; Meng Hu; Gang Wang (Advances in Atmospheric Sciences, 2015)

A genome-wide detection of copy number variation using SNP genotyping arrays in Beijing-You chickens - Wei Zhou; Ranran Liu; Jingjing Zhang; Maiqing Zheng; Peng Li; Guobin Chang; Jie Wen; Guiping Zhao (Genetica, 2014)

Age-related changes of carbon accumulation and allocation in plants and soil of black locust forest on Loess Plateau in Ansai County, Shaanxi Province of China - Taijun Li; Guobin Liu (Chinese Geographical Science, 2014)

Spatial–temporal variations of spring drought based on spring-composite index values for the Songnen Plain, Northeast China - Xiaoyan Song; Lijuan Li; Guobin Fu; Jiuyi Li; Aijing Zhang; Wenbin Liu; Kai Zhang (Theoretical and Applied Climatology, 2014)

The distribution and ultrastructure of the forming blood capillaries and the effect of apoptosis on vascularization in mouse embryonic molar mesenchyme - Guohua Yuan; Li Zhang; Guobin Yang; Jingwen Yang; Chunyan Wan; Lu Zhang; Guangtai Song; Shuo Chen; Zhi Chen (Cell and Tissue Research, 2014)

Cloning and expression characterization of the chicken Piwil1 gene - Rong Chen; Guobin Chang; Aiqin Dai; Teng Ma; Fei Zhai; Mingxiu Xia; Lu Liu; Jianchao Li; Dengke Hua; Guohong Chen (Molecular Biology Reports, 2013)

Exome Sequencing Identified NRG3 as a Novel Susceptible Gene of Hirschsprung’s Disease in a Chinese Population - Jun Yang; Shengyu Duan; Rong Zhong; Jieyun Yin; Jiarui Pu; Juntao Ke; Xuzai Lu; Li Zou; Hongmei Zhang; Zhidong Zhu; Depeng Wang; Huasheng Xiao; et al. (Molecular Neurobiology, 2013)

Cloning, characterization and widespread expression analysis of testicular piRNA-like chicken RNAs - Ying Zhang; Jianchao Li; Rong Chen; Aiqin Dai; Deqin Luan; Teng Ma; Dengke Hua; Guohong Chen; Guobin Chang (Molecular Biology Reports, 2013)

Selection of an Effective Small Interference RNA to Silence Myostatin Gene Expression in Sheep Fibroblast Cells - Jian Lu; Dan Sun; Lingyang Xu; Guobin Lu; Fuping Zhao; Caihong Wei; Li Zhang; Jiatong Ding; Bichun Li; Lixin Du (Biochemical Genetics, 2012)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

Pathogenicity of Chinese H5N1 highly pathogenic avian influenza viruses in pigeons - Beibei Jia; Jianzhong Shi; Yanbing Li; Kyoko Shinya; Yukiko Muramoto; Xianying Zeng; Guobin Tian; Yoshihiro Kawaoka; Hualan Chen (Archives of Virology, 2008)